2022
DOI: 10.1001/jamanetworkopen.2022.26561
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of a Commercial Weight Management Program Compared With a Do-It-Yourself Approach

Abstract: Key Points Question What is the efficacy at 3 and 12 months of a widely available commercial weight management program compared with a do-it-yourself approach? Findings In this 3-country randomized clinical trial that included 373 adults, reductions in weight were significantly greater at both 3 and 12 months for participants in the commercial weight management program, which included reduced requirements for dietary self-monitoring, than for participants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…This study focused on the probability of weight loss in a health care–seeking population with overweight or obesity regardless of any individual’s intention to lose weight. Several studies suggest that persons who are trying to lose weight may experience greater reductions in weight . For example, results of a 1-year randomized clinical trial among adults aged 18 to 75 years with a BMI of 25 to 45 showed that 42.8% of the treatment group enrolled in the commercial weight management program lost 5% of body weight compared with 24.7% of the control group using a do-it-yourself approach .…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the probability of weight loss in a health care–seeking population with overweight or obesity regardless of any individual’s intention to lose weight. Several studies suggest that persons who are trying to lose weight may experience greater reductions in weight . For example, results of a 1-year randomized clinical trial among adults aged 18 to 75 years with a BMI of 25 to 45 showed that 42.8% of the treatment group enrolled in the commercial weight management program lost 5% of body weight compared with 24.7% of the control group using a do-it-yourself approach .…”
Section: Discussionmentioning
confidence: 99%
“…Individual motivations for losing weight commonly include improving short‐ and long‐term health and comfort; aesthetic preferences; and reducing experiences of bias, stigma and challenges with systems maladapted to people of greater size 3,4 . Losing even 5%–10% of body weight can result in improved health outcomes, 5 and participating in organised weight‐loss programmes can increase losses 6–8 . Long‐term adherence is a key predictor of effects and is generally low across the range of weight‐loss diets 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Losing even 5%-10% of body weight can result in improved health outcomes, 5 and participating in organised weight-loss programmes can increase losses. [6][7][8] Long-term adherence is a key predictor of effects and is generally low across the range of weight-loss diets. 9,10 Studies show that maintaining weight loss after 1 year is relatively rare, 11 although a recent study identified significant weight differences 5 years after a 1-year Weight Watchers intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Efficacy of a Commercial Weight Management Program Compared With a Do-It-Yourself Approach: A Randomized Clinical Trial,” 1 published August 16, 2022, there was an error in the second paragraph of the Secondary Outcomes subsection of the Results section. The name of the measure (ie, quality of life) was inadvertently deleted.…”
mentioning
confidence: 99%
“…The name of the measure (ie, quality of life) was inadvertently deleted. It should read as follows: “At 3 months, participants in the commercial program group had significantly greater improvements than those in the DIY group in quality of life (total score, 2.49 [97.5% CI, 0.03-4.95]; P = .02; and physical function subscale, 4.10 [97.5% CI, 1.08-7.13]; P = .02).” This article has been corrected …”
mentioning
confidence: 99%